Kinetics of oxidation in fish oil and fish oil with curcumin - Salvador, Erika Eunice P. (University of the Philippines Visayas, 2018)
Various fish oil preparations, namely : pure fish oil, fish oil with 0.25% curcumin, fish oil with 0.55 curcumin, fish oil with 1% curcumin and fish oil with 1% vitamin E, were stored at storage temperatures of 4 C, 10 C, 20 C, 30 C and 45 C for 10 days. The fish oil sample used was cod liver oil. The iodometric peroxide values (PV) were determined daily and the Fourier-transform infrared (FT-IR) spectra analyzed every 2 days. Peroxide values increased as storage tme increased. Peroxide values also exhibited linearity on in peroxide value Vs time plots at a temperature range of 10 C to 45 C, indicating that the oxidation of the fish oil smaples follow first-order kinetics at 10 C to 45 C. The rate constants for each treatment increased as storage temperature increases, indicating faster oxidation of fish oil treatments at higher temperatures. Arrhenius plots were constructed and found to be linear, and the activation energies were calculated. Fish oil with 0.5% curcumin had the highest activation energy (47.95 kJ/mol) indicating that it had the slowest rate of oxidation, even slower than the positive control (fish oil 1% vitamin E, 35.68kJ/mol). Shelf life plots were also constructed for maximum peroxide values of 8 meq/kg, and were found to be linear on In t vs T. The various fish oil treatments had longer shelf lives at lower temperatures, but at an approximate room temperature of 25 C in an oxygen-exposed container, fish oil with 0.5% curcumin had the longest shelf life at 8.15 days. The FT-IR spectra of the varius fish oil treatments exhibited were determined. Characterisitc band widening at 1750 cm-1 region, indicative of the increase in other C=O-containing oxidation products was not evident due to the short storage duration. The results of this study suggest the effectivity of 0.5% curcumin in extending the shelf life of fish oil at 10 C to 45 C, and provide information to relate the shelf life of the various fish oil treatments at 10 C to 45 C for accelerated shelf life testing applications.